The effect of two pesticides (Vitavax-300 and Gaucho) on rhizobia and on the nodulation of four legumes - Miettinen, Pasi; Echegoyen, Plutarco E. (Agricultural and Food Science, 1996)
The application of seed-protecting pesticides is often a prerequisite for raising legumes in the tropics. However, these chemicals may influence the development of root nodule symbiosis. In the present study, high concentrations of Gaucho insecticide (imidacloprid) and Vitavax-300 fungicide (carboxin and captan) clearly inhibited the growth of root nodule bacterium under laboratory conditions. However, they did not effect to the nodulation or biomass production of Arachis pintoi, Arachis hypogaea, Mucuna pruriens or Desmodium ovalifolium raised in a green house in eastern Costa Rica. Explanations for these results are discussed.